Unintended consequences of measuring gestational weight gain: how to reduce weight stigma in perinatal care - Angela S. Alberga; Angela C. Incollingo Rodriguez; Taniya S. Nagpal (BMC Pregnancy and Childbirth)
Abstract In this commentary, we discuss how the practice of measuring gestational weight gain may perpetuate weight stigma and resultant discrimination if not thoughtfully assessed. We offer suggestions to reduce the likelihood of weight stigma and discrimination in perinatal care settings.